Sintesis Nanokomposit Fe3O4/SiO2/TiO2 dengan Metode Sol-Gel - Aisyiah Restutiningsih Putri Utami; Eko Sri Kunarti; M. Sulthon Nurharman Syah Putra (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2023)
The research was began with the synthesis of magnetite by reacting FeCl3.6H2O and FeSO4.7H2O by co-precipitation and sonication method. Then magnetite covered by silica was sintisized using sonication method by reacting TEOS with magnetit in base condition, and then coated by TiO2 using sol-gel method followed by calcination by using TTIP as a precusor. The X-Ray Diffractometer (XRD) were used to characterize the nanoparticles. The XRD defractofram showed the diffraction pattern 2Ã†Å¸ (o) at 25.38o, 35.881o, 38o, 38,797o, 48.26o, 54.22o, 55,4o, 63.119o, and 69.24o that based on JCPDS data No. 21-1272 that showed TiO2 anatase stucture.